2009
DOI: 10.2298/abs0903493j
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of red mullet (Mullus barbatus Linnaeus, 1758) on the Montenegrin shelf (South Adriatic)

Abstract: Red mullet, Mullus barbatus Linnaeus, 1758, is an economically very important species in trawl fisheries in the Adriatic Sea. Material for analysis was collected from October 2002 until May 2004 with a bottom trawl net from commercial trawlers on the Montenegrin shelf. Mortality of this species was analyzed for the first time in this area, sepa­rately for males and females and for both sexes together. Until now, only the spatial distribution and catch per unit of effort (CPUE) of Mullus barbatus have been stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
8
1
Order By: Relevance
“…Jukic and Piccinetti (1981) and Haïdar (1970) have reported for the Northern Adriatic Sea an estimated L50 coincident with those found in this study. While Joksimović (2005) reported for the Montenegrin shelf a L50 value of 13.54 mm, for both sexes combined, higher than those estimated in this work. Moreover, the values reported in this study are comparable with what is reported for the Southern Tyrrhenian Sea (Micale et al 2007), the Mediterranean coast of Morocco (Layachi et al 2007) and the south of France (Bougis 1952), while they are higher than those reported for the North Aegean Sea (Vassilopoulou 1992;Kokokiris et al 2014) and Cyprus (Lividas 1988) and lower than those reported for the Ionian West Sea (Tursi et al 1994), the Aegean Turkish coast (Metin 2005), the Northern Tyrrhenian Sea (Voliani et al 1998) and the Tunisian coast (Gharbi and Ktari 1981).…”
Section: Discussioncontrasting
confidence: 82%
“…Jukic and Piccinetti (1981) and Haïdar (1970) have reported for the Northern Adriatic Sea an estimated L50 coincident with those found in this study. While Joksimović (2005) reported for the Montenegrin shelf a L50 value of 13.54 mm, for both sexes combined, higher than those estimated in this work. Moreover, the values reported in this study are comparable with what is reported for the Southern Tyrrhenian Sea (Micale et al 2007), the Mediterranean coast of Morocco (Layachi et al 2007) and the south of France (Bougis 1952), while they are higher than those reported for the North Aegean Sea (Vassilopoulou 1992;Kokokiris et al 2014) and Cyprus (Lividas 1988) and lower than those reported for the Ionian West Sea (Tursi et al 1994), the Aegean Turkish coast (Metin 2005), the Northern Tyrrhenian Sea (Voliani et al 1998) and the Tunisian coast (Gharbi and Ktari 1981).…”
Section: Discussioncontrasting
confidence: 82%
“…The Φ′ values from LFDA were significantly higher compared to those derived from the otolith reading for both sexes. The female Φ′ values calculated from the otolith reading ranged between 1.848 36 and 2.686 37 , while those from LFDA ranged between 2.051 38 and 2.763 8 . The male Φ′ values calculated from the otolith reading ranged between 1.937 39 and 2.468 40 , while those from the LFDA ranged between 1.952 38 and 2.554 41 .…”
Section: Resultsmentioning
confidence: 97%
“…The female Φ′ values calculated from the otolith reading ranged between 1.848 36 and 2.686 37 , while those from LFDA ranged between 2.051 38 and 2.763 8 . The male Φ′ values calculated from the otolith reading ranged between 1.937 39 and 2.468 40 , while those from the LFDA ranged between 1.952 38 and 2.554 41 . In addition, the Φ′ values grouped by area (Mediterranean sub-region WM: Western Mediterranean; CM: Central Mediterranean; EM: Eastern Mediterranean) showed significant differences.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The discrepancies between the mortality rates from different localities can probably be attributed to various factors such as different ecological conditions and intensive fishing activities between the localities and unequal precision of employed various methods (Joksimović et al, 2009) Some of the results in previous studies about spawning period and length at first maturity of S. japonicus in different localities are given in Table 6. Spawning periods of fish vary with respect to their species and could attributed to the ecological differences such as stagnant or running water, temperature and quality of food (Nikolsky, 1963).…”
Section: Discussionmentioning
confidence: 99%